New Onset Systemic Sclerosis-Polymyositis Overlap Syndrome FollowingSecond Dose of COVID-19 Vaccine – A Case Report - Andi Raga Ginting (Indonesian Rheumatology Associantion, 2025)
Background: Coronavirus 2019 has been declared as a global emergency by theWorld Health Organization. Vaccination has been shown to be crucial during theCOVID-19 pandemic. However, as global vaccination programs are implemented,a number of COVID-19 vaccine-related side effects have lately been recorded,including new-onset autoimmune disease. Overlap syndrome is a medicaldisorder in which a patient has symptoms of at least two or more autoimmuneconnective tissue diseases that meet the clinical criteria. Case Presentation: A33-years-old woman with history of Graves’ disease presented with myalgia,proximal superior and inferior extremities muscle weakness, skin thickening inface and both superior and inferior extremities following the second dose ofinactivated whole virus COVID-19 vaccine. ANA test was found to be positive withno specific antibody related to disease and there was an increase in muscleenzyme. The patient was treated with combination of mycophenolic acid,methylprednisolone, nifedipine, vit D3 and curcuma. After 4 months of treatment,patient showed clinical improvement and decrease in muscle enzymes.Conclusion: Systemic Sclerosis-Polymyositis overlap syndrome is anautoimmune connective tissue disease that is frequently encountered inconjunction with myositis. The causes of autoimmune disease are multifaceted,involving genetic, environmental factors, and overstimulation of the immuneresponses. The relationship between COVID-19 vaccination and autoimmunedisease, especially systemic sclerosis-polymyositis overlap syndrome, stillrequires further study due to lack of reported evidence.